The Rapidly Changing Treatment Landscape of Systemic Therapy for HER-2 Positive Metastatic Breast Cancer - Larissa Russo-Vorms; Christoforos Astaras; José Sandoval; Maxime Borgeaud; Alexandre Bodmer (healthbook TIMES. Oncology Hematology)
Human epidermal growth factor receptor 2 (HER-2) overexpressed breast cancer has traditionally been considered as an aggressive disease with high risk of systemic and brain metastases and poor prognosis. Nowadays, we have many HER-2 targeting treatments that have radically changed patients’ outcomes. Among the oldest ones, trastuzumab, pertuzumab, lapatinib and trastuzumab-emtansine have been for some years the backbone of established therapies. New drugs, such as tucatinib, trastuzumab-deruxtecan, pyrotinib, neratinib and margetuximab, have recently joined the therapeutic arsenal, revolutionizing the therapeutic field of this disease. Many other drugs are currently under development and give hope, with encouraging results to heavily pretreated patients or those with central nervous system metastasis.